2018
DOI: 10.1016/j.jaci.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of allergen-specific T follicular helper cell counts with specific IgE levels and efficacy of allergen immunotherapy

Abstract: , the Karolinska Institutet Center for Innovative Medicine (Y.T.B.), the Swedish Childhood Cancer Foundation (J.-I.H., Y.T.B., M.M.), as well as the Stockholm County Council, the Swedish Cancer Foundation, and the Swedish Research Council (J.-I.H., Y.T.B.), the Cancer and Allergy Foundation of Sweden (J.-I.H.), the German Ministry of Education and Research (grant no. BMBF 01EO1303), and the German Research Foundation (grant no. SFB1160, TP1; S.E.). B.T. is also supported by a doctoral student scholarship from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 19 publications
4
63
0
Order By: Relevance
“…Normal ethmoid sinus mucosal samples unrelated to the lesions were obtained from control subjects during surgery. Atopic status was evaluated by a skin‐prick test with a panel of aeroallergens common in our area . Allergic rhinitis was diagnosed on the concordance between a typical history of allergic symptoms and the atopy test results .…”
Section: Methodsmentioning
confidence: 99%
“…Normal ethmoid sinus mucosal samples unrelated to the lesions were obtained from control subjects during surgery. Atopic status was evaluated by a skin‐prick test with a panel of aeroallergens common in our area . Allergic rhinitis was diagnosed on the concordance between a typical history of allergic symptoms and the atopy test results .…”
Section: Methodsmentioning
confidence: 99%
“…Skin prick tests with a panel of 19 inhalant allergens common in our region was performed, as previously described, 6 and additional information is provided in the Methods section in this article's Online Repository at www.jacionline.org.…”
Section: Allergen Testmentioning
confidence: 99%
“…3 Several studies using mouse models demonstrated that T FH cells orchestrated systemic IgE production in patients with allergic asthma. 4,5 Recently, we have found that increased numbers of peripheral type 2 T FH (T FH 2) cells positively correlated with upregulated IgE in patients with AR, 6 suggesting a skewed polarization of T FH 2 cells in promoting IgE production in patients with AR.…”
mentioning
confidence: 99%
“…Patients undergoing septoplasty because of anatomical variations and without any other sinonasal diseases were enrolled in the study as controls. Atopic status was evaluated by a skin prick test with a panel of aeroallergens common in our area . Allergic rhinitis was diagnosed on the concordance between a typical history of allergic symptoms and the atopy test results .…”
Section: Methodsmentioning
confidence: 99%
“…Atopic status was evaluated by a skin prick test with a panel of aeroallergens common in our area. 24 Allergic rhinitis was diagnosed on the concordance between a typical history of allergic symptoms and the atopy test results. 25 The diagnosis of asthma was made based on Global Initiative for Asthma guidelines.…”
Section: Patientsmentioning
confidence: 99%